Literary Heritage of Sharof Rashidov - Ochilova Bakhti Murodovna (Scientific Trends, 2024)
This article examines the influence of literary characters created by Sharof Rashidovich Rashidov on the formation of values among Uzbek youth in the context of globalization. It highlights how Rashidov’s characters, embodying traditional values and cultural ideals, serve as moral guides and examples for young people navigating the complexities of a globalized world. The article also explores how Rashidov’s works contribute to the preservation and transmission of traditional values in modern society. Through an analysis of his key characters, the article underscores the role of literature in shaping cultural identity and fostering a sense of belonging among youth in a rapidly changing world. By intertwining universal themes with local traditions, Rashidov’s works continue to influence generations, helping them maintain cultural continuity while embracing global perspectives.
Keywords: Sharof Rashidovich Rashidov, “Kashmir Song,” “Stronger than the Storm,” literary characters, Uzbek youth, value formation, globalization, cultural identity, moral guidance.